2010
DOI: 10.1111/j.1751-1097.2009.00689.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Inactivation of Conidia of the Fungi Metarhizium anisopliae and Aspergillus nidulans with Methylene Blue and Toluidine Blue

Abstract: Antimicrobial photodynamic treatment (PDT) is a promising method that can be used to control localized mycoses or kill fungi in the environment. A major objective of the current study was to compare the conidial photosensitization of two fungal species (Metarhizium anisopliae and Aspergillus nidulans) with methylene blue (MB) and toluidine blue (TBO) under different incubation and light conditions. Parameters examined were media, photosensitizer (PS) concentration and light source. PDT with MB and TBO resulted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
46
2
22

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(82 citation statements)
references
References 47 publications
1
46
2
22
Order By: Relevance
“…This effect was previously observed in APDT with MB and TBO on Aspergillus nidulans conidia [32]. As opposed to what was observed in ungerminated microconidia, washing the germinated microconidia did not reduce the effect of the APDT (at fluence of 15 J cm -2 ) with all PS on the three Fusarium species.…”
Section: Discussioncontrasting
confidence: 37%
“…This effect was previously observed in APDT with MB and TBO on Aspergillus nidulans conidia [32]. As opposed to what was observed in ungerminated microconidia, washing the germinated microconidia did not reduce the effect of the APDT (at fluence of 15 J cm -2 ) with all PS on the three Fusarium species.…”
Section: Discussioncontrasting
confidence: 37%
“…Previous studies have reported the use of APDT with different PSs to kill fungi of several genera, including Aspergillus, Candida, Cryptococcus, Metarhizium, and Trichophyton (15)(16)(17)20). Data regarding the photodynamic inactivation of plant-pathogenic fungi are scarce, and most of those studies were performed by using natural compounds as PSs.…”
mentioning
confidence: 99%
“…In comparison with currently used fungicides, the multiple and variable targets of reactive oxygen species reduce the chance of selecting tolerant microorganisms. An additional advantage of APDT is that unlike many conventional fungicides that kill only metabol-ically active cells, it is able to kill both metabolically active and dormant or quiescent structures such as conidia (16,20).…”
mentioning
confidence: 99%
See 2 more Smart Citations